Functional connectivity between posterior hippocampus and retrosplenial complex predicts individual differences in navigational ability. Issue 7 (18th April 2016) - Sulpizio, Valentina; Boccia, Maddalena; Guariglia, Cecilia; Galati, Gaspare
ABSTRACT: Individuals vary widely in their ability to orient and navigate within the environment. Previous neuroimaging research has shown that hippocampus (HC) and scene‐responsive regions (retrosplenial complex [RSC] and parahippocampal gyrus/parahippocampal place area [PPA]) were crucial for spatial orienting and navigation. Resting‐state functional connectivity and a self‐reported questionnaire of navigational ability were used to examine the hypothesis that the pattern of reciprocal connections between these regions reflects individual differences in spatial navigation. It was found that the functional connectivity between the posterior HC and RSC was significantly higher in good than in poor navigators. These results confirmed the crucial role of hippocampal and extra‐hippocampal regions in spatial navigation and provided new insight into how spontaneous brain activity may account for individual differences in spatial ability. © 2016 Wiley Periodicals, Inc.